GMP Compliant Production of a Cryopreserved Adipose-Derived Stromal Cell Product for Feasible and Allogeneic Clinical Use - Mandana Haack-Sørensen; Ellen Mønsted Johansen; Lisbeth Drozd Højgaard; Jens Kastrup; Annette Ekblond (Stem Cells International)
The emerging field of advanced therapy medicinal products (ATMP) holds promise of treating a variety of diseases. Adipose-derived stromal cells (ASCs) are currently being marketed or tested as cell-based therapies in numerous clinical trials. To ensure safety and efficacy of treatments, high-quality products must be manufactured. A good manufacturing practice (GMP) compliant and consistent manufacturing process including validated quality control methods is critical. Product design and formulation are equally important to ensure clinical feasibility. Here, we present a GMP-compliant, xeno-free, and semiautomated manufacturing process and quality controls, used for large-scale production of a cryopreserved off-the-shelf ASC product and tested in several phase I and II allogeneic clinical applications.